Tafsir Tahlili: Analisis Surah al-Maidah Ayat 6: Tafsir Tahlili: Analysis of Surah al-Maidah Verse 6 - Mukhamat Alfi Zaini; Ahmad Zarkasyi Noor Wahid (DIRASAH: Jurnal Kajian Islam, 2025)
Indonesia with multicultural characteristics has a diversity of dynamics of social life patterns both in opinion and culture. The opinion that developed and popular in Indonesia in the legal area is the opinion of madzahib al-arba'ah (Hanafi, maliki, shafi'I, and Hanbali). So that in the context of making decisions related to developing problems, not only in the area of worship, the opinion of madzahib al-arba'ah is always the primary reference and reference.  However, not a few people who are able to understand these differences, giving rise to polemics and rumors related to the validity of worship among others. this study aims to explain the content of surah al-Maidah verse 6 by using the tahlili method. This research is qualitative library research with descriptive-analytical method to explain the content of surah al-Maidah verse 6. The exposure of Surah al-Maidah verse 6 will be discussed from several aspects, both the discussion of vocabulary followed by the global meaning of the verse, the exposure of asbab nuzul, and analysis related to the law contained therein. The result of this study is the significance of surah al-maidah verse 6 in delivering the validity of an ubudiyah. Ubudiyah (prayer) in the territory of Islam is a sacred thing, where every adherent always does it in any conditions and circumstances. Differences in madzhab imams (ikhtilaf al-madzhab) in understanding the nashah surah al-maidah verse 6 is a Grace (blessing) for religious believers, where they can follow the opinions of other madzhab imams in certain conditions.